Self-integrity and family support as assets for resilient urban at-risk youth - Chong, Sheau Tsuey; Abdul Rahim, Samsudin; Subhi, Nasrudin; Abdul Kadir, Nor Ba'yah; Jusoff, Kamaruzaman; Abdul Mutalib, Mimi Hanida; Wan Mahmud, Wan Amizah; Chang, Peng Kee; Ismail, Rokiah; Mustapha, Zaidah; Mohd, Rusyda Helma; Ismail, Rozmi; et al. (IDOSI Publications, 2011)
While most of the Malaysian youth literature view young people as problematic and chaotic, this research aims to highlight that at-risk young Malaysians also possessed developmental assets which could contribute to their resilience level. This research explores at-risk youth resilience and predicts which protective factor is the most utilized. To be specific, at-risk young people who lived at the outskirt of metropolitan Kuala Lumpur were targeted. Survey designed method on 744 young people of Pantai Dalam, Kuala Lumpur who lived in low cost government flats. Integrity and family support predict levels of resilience. The results show that under disadvantaged environment, family support could sustain young people's resiliency in facing difficulties of life. This research argues that internal asset and family institution contributes to at-risk young people's internal defense system. This research recommends that future research should study the quality of family support and reveal the quality facets of resilience.